2018
DOI: 10.3390/su10072551
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Efficiency of Photovoltaic Power Plants in China—A Comparative Study of Different Economic Zones and Plant Types

Abstract: In this paper we study and compare the environmental efficiency of 118 photovoltaic (PV) plants in China. Drawing on the nonparametric data envelopment analysis (DEA) method, our study takes the initiative to take the insolation, annual sunshine duration, and covering area as input variables into account, as well as the installed capacity, annual electricity generation, CO2 emission reduction, and coal saving as output variables, to provide a unified measure of environmental efficiency of PV plants in China. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…The study concluded that it is necessary to expand the scope of the Clean Air Act (CAA) in the United States to control carbon dioxide emissions. Drawing on the nonparametric DEA method, You takes the initiative to take the insolation, annual sunshine duration, and covering area as input variables into account, as well as the installed capacity, annual electricity generation, CO 2 emission reduction, and coal saving as output variables, to provide a unified measure of environmental efficiency of PV plants in China [34]. Zhang et al [35] believed that attention should be paid to the internal resource loss and external environmental damage caused by environmental pollution waste, and developed the "internal loss-external damage" (ILD) method for evaluating the environmental performance of coal-fired power plants, which effectively identified the key environmental pollution impact factors and successfully quantified internal resource loss costs and environmental damage costs.…”
Section: Determination Of Evaluation Methodsmentioning
confidence: 99%
“…The study concluded that it is necessary to expand the scope of the Clean Air Act (CAA) in the United States to control carbon dioxide emissions. Drawing on the nonparametric DEA method, You takes the initiative to take the insolation, annual sunshine duration, and covering area as input variables into account, as well as the installed capacity, annual electricity generation, CO 2 emission reduction, and coal saving as output variables, to provide a unified measure of environmental efficiency of PV plants in China [34]. Zhang et al [35] believed that attention should be paid to the internal resource loss and external environmental damage caused by environmental pollution waste, and developed the "internal loss-external damage" (ILD) method for evaluating the environmental performance of coal-fired power plants, which effectively identified the key environmental pollution impact factors and successfully quantified internal resource loss costs and environmental damage costs.…”
Section: Determination Of Evaluation Methodsmentioning
confidence: 99%
“…Sustainability 2020, 12, x 4 of 29 of solar minimizes energy cost from the utility grid [44]. A comparative study of different economic zones and plant types has been presented [45] to exhibit the environmental efficiency of photovoltaic power plants in China. A case study has been presented [46] to emphasize the techno-economic feasibility assessment of grid-connected PV systems for residential buildings in Saudi Arabia.…”
Section: Solar Pv Deployment-global Scenariomentioning
confidence: 99%
“…For instance, the geographical location of the application site, where the longer sunshine hours of high-latitude regions result in better EO of PV modules than shorter sunshine hours of low-latitude regions [40]. You et al [3] compared the environmental efficiency of four PV plants in China, including a mountain plant, desert plant, rooftop plant, and complementary plant. Taking into consideration several input variables (i.e., insolation, covering area, and annual sunshine duration) and output variables (i.e., annual electricity generation, the installed capacity, coal saving, and CO 2 emission reduction), the authors found that there is a difference in the performance of PV plants.…”
Section: Related Literaturementioning
confidence: 99%
“…The construction sector is renowned for its high consumption of energy and natural resources [1]. It is reported to be responsible for almost 30% of annual greenhouse gas (GHG) emissions and 34 × 10 6 Gigawatt-hours of total energy consumption worldwide, making it one of the top contributors to pollution [2], and causing several environmental impacts, such as global warming [3]. Soaring rates of urbanization will also exacerbate the issue even further, leading to an increase in energy consumption and GHG emissions [4].…”
Section: Introductionmentioning
confidence: 99%